Rationality in Religious Epistemology: An Analysis of Abdul-Karim Soroush’s View on the Transformation of Contemporary Religious Thought - Abd Basit; Anwar Sanusi; Theguh Saumantri (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
The rapid development of science and social changes in the contemporary era have created a tension between traditional religious thought and the modern world. Religion is often viewed as a static system, while science and technology continue to evolve. This research aims to explore how Soroush distinguishes between religion as eternal revelation and religious knowledge as a product of human effort that can evolve in response to changes over time. The methodology used in this research is qualitative analysis with a descriptive-analytical approach. The findings indicate that Soroush emphasizes the importance of intellectual humility in facing the plurality of religious interpretations, viewing religious knowledge as an ongoing process that evolves according to social and scientific changes without compromising the essence of revelation. Academically, this research contributes to the study of religious epistemology by providing insights into how Soroush’s thought can help redefine the relationship between religion and science in the context of the contemporary world, as well as renewing religious understanding more flexibly and dynamically.